THE ROLE OF HISTORY TEACHERS IN INSTILLING A SENSE OF NATIONALISM IN THE CLASS X STUDENTS AT SMA NEGERI 15 GOWA - Salam, Supardi (International Conference on Cultural Studies, 2018)
This study aims to obtain more information about the role of history teachers in instilling a sense of nationalism in the class X students in SMA Negeri15 Gowa. The type of this research is qualitative descriptive which become the source of research data is the history teacher amounted to one person, the students of class X SMA Negeri15 Gowaand principal SMA Negeri15 Gowa. Data collection methods used are observation, interview and documentation. The results showed that the role of history teacher in instilling a sense of nationalism in the class X students in SMA Negeri15 Gowa is the role of history teachers in instilling a sense of student nationalism are teachers as role models, teachers as inspirators, teachers as motivators, teachers as a dinamicators, teachers as evaluators. While the obstacles encountered by history teachers in instilling a sense of nationalism in students include: different student backgrounds, technological developments that also influence the pattern of student thinking, the influence of mass media, and school facilities that have not been fully adequate in supporting learning history and the lack of meeting hours for the subjects of history. The history teacher's efforts in instilling a sense of nationalism to students that include: learning history (planning, implementation, evaluation) and extracurricular activities. At the planning stage consisting of syllabus and RPP designed by the history teacher.